Strategi Dalam Meningkatkan Kesejahteraan Ekonomi Melalui Optimalisasi Pengelolaan Zakat Profesi Di BAZNAS Ponorogo - Syamsuri Syamsuri; Muhammad Yogi Ma’aldini (Institut Agama Islam Negeri Madura, 2018)
In the last few decades, the potential of zakat funds in Indonesia in recent years has reached 300 trillion. The Zakah of profession is one of the zakat funds collected in it. with the consciousness of workers and government employees allowing their salaries to be reduced to zakat. However, in the reality zakat funds collected from the Muslims have not been properly managed by the management of zakat. Evidently there are many socio-economic imbalances, low nutritional quality everywhere and prosperity is only enjoyed by certain groups of people only. This means that the manager has not had a good strategy in solving the problem of economic disparities among the surrounding Muslim community. Ttherefore by using a descriptive qualitative approach where the source data obtained through observation, interviews and documentation and the three data are analyzed inductively. Finally this article found three strategies that have been done by Baznas ponorogo to improving the welfare of society through zakat profession namely: first, by way of zakat publication. Second, the action in the management of zakat and third, the administration of zakat management.